In Vivo Biodegradation and Biocompatibility of PEG/Sebacic Acid-Based Hydrogels using a Cage Implant System - Kim, Jinku (2010)
Comprehensive in vivo biodegradability and biocompatibility of unmodified and Arg-Gly-Asp (RGD) peptide-modified PEG/Sebacic acid based hydrogels were evaluated and compared to the control material poly(lactide-co-glycolide) (PLGA) using a cage implantation system, as well as direct subcutaneous implantation for up to 12 weeks. The total weight loss after 12 weeks of implantation for unmodified PEGSDA and RGD-modified PEGSDA in the cage was approximately 42% and 52%, respectively, with no statistical difference (p> 0.05). The exudate analysis showed that PEGSDA hydrogels induced minimal inflammatory response up to 21 days following implantation, similar to the controls (empty cage and the cage containing PLGA discs). Histology analysis from direct subcutaneous implantation of the hydrogels and PLGA scaffold showed statistically similar resolution of the acute and chronic inflammatory responses with development of the fibrous capsule between the PEGSDA hydrogels and the control (PLGA). The cage system, as well as the histology analysis, demonstrated that the degradation products of both hydrogels, with or without RGD peptide modification, are biocompatible without statistically significant differences in the inflammatory responses, as compared to PLGA.